Challenges of Female Activists and the Use of Social Media for 2023 Presidential Election in Nigeria - Bolanle Olayinka Idowu; Moshood Babatunde Abdul-Wasi; Olayinka Babatunde Adebogun (Polit Journal Scientific Journal of Politics, 2026)
Social media have galvanising impact on feminists’ issues, serving as tools for political communication and mobilisation. In amplifying gender equity in political seats, Nigerian female activists were often subjected to multiple barriers, hindering the attainment of the SDG5. Previous studies in communication of gender equity have focused on how the Nigerian female activists utilised the use of social media to raise this call. However, there is a dearth of literature on the challenges encountered by female activists while engaging social media for more women participation in politics. This study was, therefore, designed to examine the challenges encountered by female activists in the use of Social Media for 2023 Presidential election in Nigeria, with a view to establishing the extent of difficulties faced. Uses and Gratification and Patriarchy Hegemony theories were used as the framework while the qualitative design was adopted. Datareportal 44.7 percent of Nigeria’s social media users were female out of which existed Nigerian female activists. Fifteen female activists were purposively selected with snowball sampling also adopted. In-depth interview was adopted in eliciting responses using interview guide as research instrument. The findings reveal the female activists encountered cyber bullying and online threats, disinformation and misinformation, tribal bullying and patriarchal dominance, defamatory comments, hacking and account and suspension to the extent of having technical and financial barriers.